Entrepreneurial Reinvestment: Local Governance, Ownership, and Financing Matter—Evidence from Vietnam. (29th October 2018) - Nguyen, Bach
Abstract: This study investigates the relative importance of local governance and external financing on small firms' reinvestments. Using a set of more than 300, 000 Vietnamese firm‐level observations from 2006 to 2015, this study finds that local governance quality is positively associated with small firms' reinvestments. However, regarding external funds, only informal finance is positively associated with reinvestments while government loans and bank loans serve as substitutes to reinvestments. Also, this study suggests that there is significant heterogeneity among ownership sectors and between micro‐enterprises and small firms in the way they value the relative importance of local governance arrangements and financing sources.